2012
DOI: 10.7202/1012541ar
|View full text |Cite
|
Sign up to set email alerts
|

Ocularcentric Labour:  “you don’t do this for money”

Abstract: This article is a response to Lansbury’s call (2009) in this journal for a re-conceptualization of work and employment. It supports Lansbury’s belief that the employment relationship cannot be understood in isolation from wider social change. Building on the tradition of emotional labour and aesthetic labour, this study introduces theoretically and empirically the concept of “ocularcentric labour” (the worker seeking the adoring gaze of the client as the primary employment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…Research has pointed to an increasing influence of physique on identity, self-concept and physical capital. Sappey and Maconachie (2012) suggested that the body is a central concept to self-identity, with some individuals increasingly defining themselves through their physique. Frew and McGillivray (2005) proposed that this concept of the 'body aesthetic' increasingly represents the physical capital of the individual in contemporary society.…”
Section: Physique In Health and Fitness Centresmentioning
confidence: 98%
See 3 more Smart Citations
“…Research has pointed to an increasing influence of physique on identity, self-concept and physical capital. Sappey and Maconachie (2012) suggested that the body is a central concept to self-identity, with some individuals increasingly defining themselves through their physique. Frew and McGillivray (2005) proposed that this concept of the 'body aesthetic' increasingly represents the physical capital of the individual in contemporary society.…”
Section: Physique In Health and Fitness Centresmentioning
confidence: 98%
“…First, staff may facilitate the customers' attainment of a more desired physique outcome through their role as class instructors or personal trainers, with Sappey and Maconachie (2012) suggesting that the fitness workers' appearance, or more precisely their physical capital, helps to retain and motivate clients. Second and conversely, the presence of staff with attractive physiques (typical of health and fitness centres) may create a context of upward social comparison (Dijksterhuis et al, 1998;Festinger, 1954) where the customer evaluates their physique negatively against the staff member.…”
Section: Background To the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Neste conceito, o personal trainer com aparência física desejável pelo consumidor, como citado acima, pode motivá-lo a ter intenção de compra dos seus serviços (TianCole & Cromption 2003;Sappey & Maconachie, 2012). Assim alcança-se a quinta e última hipótese, proposta nessa pesquisa.…”
Section: Aparência Físicaunclassified